Is assurance on risk management systems relevant for bankers' decisions?. (December 2021) - Quick, Reiner; Gauch, Kevin
Abstract: Risk management systems (RMS) are an essential element of corporate governance and support companies in managing the omnipresent internal and external risks. Assurance on such systems can support such efforts and add further benefits. This study investigates the impact of RMS assurance on the perceptions and decisions of German bankers, and analyzes whether the assurance provider and the assurance level are relevant to them. We conducted an experiment with 145 bankers, using ANOVA to analyze their reliance on the hypothetical company's RMS and their decisions regarding lending, recommending investments, and investing in stocks. A 2×2+1 between-subjects design was chosen, and we manipulated the assurance provider (audit firm vs. third-party provider) and the assurance level (limited vs. reasonable), and added a control condition with no assurance. Our results indicate that RMS assurance positively influences banker perceptions and decisions, whereas the assurance provider and assurance level has no statistically significant impact on them.